Advances in mergers and acquisitions. Vol. 2 - Gregory, Alan, 1954-; Cooper, Cary L. (Emerald, 2003)
Bringing together academics from various disciplines, these papers integrate the disparate but growing body of literature on mergers and acquisitions. The series is published to explain and discuss the unsatisfactory outcomes that result from many poorly conceived mergers.
Keywords: Consolidation and merger of corporations.; elektronické knihy; electronic books